Foreign acquisition, plant survival, and employment growth - Roger Bandick; Holger Görg (Institute for the Study of Labor (IZA), 2009)
This paper analyses the effect of foreign acquisition on survival probability and employment growth of target plant using data on Swedish manufacturing plants during the period 1993-2002. An improvement over previous studies is that we take into account firm level heterogeneity by separating the targeted plants into those within Swedish MNEs, Swedish exporting non-MNEs, and purely domestic firms before foreign takeover. The results, controlling for possible endogeneity of the acquisition dummy using an IV and propensity score matching approach suggest that acquisition by foreign owners increases the lifetime of the acquired plants only if the plant was an exporter. The effect differs depending on whether the acquisition is horizontal or vertical. We also find robust positive employment growth effects only for exporters, and only if the takeover is vertical, not horizontal.
urn:nbn:de:101:1-2009062270
Keywords: F23; L23; 330; Acquisitions; plant survival; employment growth; multinational enterprises; Beschäftigungseffekt; Übernahme; Multinationales Unternehmen; Unternehmensentwicklung; Schätzung; Verarbeitendes Gewerbe; Schweden